Factor Affecting Trust and Use of E-Government: The Case of Banda Aceh City, Aceh Province - Syahroni, Faez; Ardiansyah; Pribadi, Ulung; Rafi, M; Amri, Pahmi (Universitas Pancasakti Tegal, 2023)
In the government sector, E-Government has become part of innovation. The use of E-Government is necessary to maintain government transparency. In Banda Aceh City, Aceh Province, Indonesia, this study tries to capture the phenomenon of the factors that influence trust and use of E-Government. The purpose of this research is to learn about the elements that influence trust and adoption of E-Government in the Banda Aceh region through quantitative research. This research is included in the category of survey research. This study found that two variables have positive and significant implications for other variables, namely the benefit variable has significant implications for trust in e-government, and the trust variable in e-government has significant implications for the use of e-government. Meanwhile, three other variables that have no significant implications are organizational factors, technological factors, and risk factors for public trust in the use of E-Government by the government. This study also has limitations, such as considering the positive impact on the use of e-government in the Banda Aceh Region, rather than the problem of only using e-government in the Banda Aceh Region of Aceh Province. The time limit associated with data collection is another weakness of this study.